Applying Closing Phase-Angle Control Technique in Bounce Reduction of AC Permanent Magnet Contactor - Chieh-Tsung Chi (Active and Passive Electronic Components)
A new low-cost electronic control circuit actuator is proposed for minimizing the bouncing times of an AC permanent magnet (PM) contactor after two contacts closing. The proposed new actuator overcomes the bouncing problem of an uncontrollable restrictions imposed by previously conventional AC electromagnetic (EM) contactor based on the minimization of kinetic energy prior to two contacts impact. By choosing the closing phase angle of coil voltage on purpose, the bouncing problems of the movable contact during the closing process are then overcome. The using life of contacts is then prolonged and their operating reliability is improved as well. In order to validate the feasibility and effectiveness of the proposed method here, several simulation and experimental procedures were performed on a prototype of AC PM contactor in the laboratory. Testing results actually showed that bouncing problem of contactor's contacts during the closing process was to be controlled by using the proposed technology.